Island Book one, Shipwreck - Korman, Gordon (New York : Scholastic, 2001)
Six kids, Nick, J.J., Will, Lyssa, Charla, and Ian, are thrown together against their will on a small boat that will make a one-month journey on the Pacific Ocean. They have all been sent for different reasons. Luke is taking his only choice besides being sent to a juvenile detention facility for a crime he didn't commit. Will and Lyssa are quarreling siblings sent by their parents, who hope the trip will teach them to get along better. J.J. was sent by a movie-star father after he pulled one two many pranks. Ian's parents hoped to cure him of his TV addiction. Charla was sent because she was having an athletic "burnout." But these six totally different kids have to learn to work together to survive a vicious storm and a shipwreck that leave them stranded in the middle of the ocean with no food, no water, and almost no hope for survival.
"An Apple Paperback."
610
Accelerated Reader AR
Keywords: Shipwrecks -- Juvenile fiction; Survival -- Juvenile fiction